Tanggung Jawab Pemegang Saham Perseroan Terbatas di Indonesia Menurut Hukum Positif Indonesia - Sistiya Astari, Maria Wulan; Mayasari, I Dewa Ayu Dwi (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
The purpose of this paper is basically to know and understand in more detail the responsibilities of the shareholders of a limited liability company. This research uses a normative research method using a statue approach and conceptul aprroach. The result of the research is that the Company as a legal entity has assets that are separate from its shareholders. This separation of assets is also accompanied by limited liability. Shareholders of the company have limited liability  the provisions regulated under Article 3 paragraph (2) of the Company Law in which shareholders with limited liability can change to unlimited if the shareholders commit bad faith which then causes the limited liability to change to unlimited so that the personal assets of the shareholders are not separated from the assets of the limited liability company.